Development of the structure of the geospatial database for beekeeping - Domina, I. (Land Management, Cadastre and Land Monitoring, 2020)
Abstract. The work draws attention to the importance of beekeeping to provide the population of Ukraine with food, as pollination is necessary to obtain many foods and more. The method of collecting information using Remote sensing is mentioned. And how is the operational approach to identifying possible locations of apiaries. The main problems of accumulation of a large amount of data are revealed, namely the methods of storing geospatial data. The main purpose is to develop a model of geographic information database that will store information about land (areas) safe and dangerous for bees. The necessity of such a database is substantiated, its constituent parts (land plots, safe zones with fodder base of beekeeping, buffer zones around dangerous objects, annual and perennial vegetation) are defined and described. The paper also gives examples of similar geoinformation databases of the European Union, the purpose of which is to monitor the forest stands of Europe (The Forest Information System for Europe). An example of application of the developed database in the country is presented and the direction of development with the help of geoinformation technologies is determined.Keywords. Geospatial database, fodder base of beekeeping